The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.enconman.2018.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of a heating tower heat pump and an air-source heat pump: A comprehensive modeling and simulation study

Abstract: The heating tower heat pump (HTHP) is proposed as an alternative to the conventional air-source heat pump (ASHP). To investigate the performance improvements of the HTHP over the ASHP, a comprehensive comparison between the two systems was carried out based on a simulation study. Physics-based models for the ASHP and HTHP were developed. The performance of the ASHP under frosting conditions was corrected with a newly developed frosting map, and the regeneration penalization was considered for the HTHP. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…At the same time, the risk of Legionella can be eliminated via supplementary heating or point of use heating (Lund et al, 2014;Lee, 2018). By reviewing literature regarding the low-temperature heating concept, supply temperatures of 40 and 11-12 • C are selected for heating and cooling, respectively (Nordman et al, 2012;Huang et al, 2019).…”
Section: Hp Systemmentioning
confidence: 99%
“…At the same time, the risk of Legionella can be eliminated via supplementary heating or point of use heating (Lund et al, 2014;Lee, 2018). By reviewing literature regarding the low-temperature heating concept, supply temperatures of 40 and 11-12 • C are selected for heating and cooling, respectively (Nordman et al, 2012;Huang et al, 2019).…”
Section: Hp Systemmentioning
confidence: 99%
“…They not only provide ecological solutions for heat generation, but also increase energy independence [6]. However, there are still some shortcomings limiting the further development of solar thermal utilization technology and ASHP technology, such as the intermittence and low energy density of solar energy [7] and the phenomenon that the evaporator of the ASHP may be frosted in a low temperature environment, which leads to a decrease in heating capacity and Coefficient of Performance (COP) [8]. For the purpose of effectively solving the frosting problem in ASHP applications, the heat-source tower technology was put forward [9].…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [12] constructed an open-type heat-source tower heat pump (OHTHP) test device and discovered that the system has a good heating effect and almost completely avoided the ASHP frosting problem. Huang et al [8] used a numerical method to compare and analyze the performance of OHTHP and traditional ASHP, and discovered that compared with traditional ASHP, the efficiency of OHTHP in summer and winter increased by 23.1% and 7.4%, respectively. Lu et al [13] established the prediction correlation of heat and mass transfer of an open-type heat-source tower by theoretical analysis and a numerical method.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2019a) carried out a large-scale comprehensive performance evaluation of the HTHPs in 869 typical locations in the warm, mixed and cool climate zones over the world; the results show that the HTHPs have excellent performance in the warm and mixed climate zones and also applicable in the cool climate zone. To investigate the performance improvements of the HTHP over the air-source heat pump, a comprehensive comparison between the two systems was carried out based on a simulation study by Huang et al (2019b); it was found that the HTHP achieves an increase of 7.4% in efficiency that air-source heat pump in winter.…”
Section: Introductionmentioning
confidence: 99%